2011
DOI: 10.1186/1471-2334-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Antibody dynamics and spontaneous viral clearance in patients with acute hepatitis C infection in Rio de Janeiro, Brazil

Abstract: BackgroundThe anti-HCV antibody response has not been well characterized during the early phase of HCV infection and little is known about its relationship to the clinical course during this period.MethodsWe analyzed serial anti-HCV antibodies longitudinally obtained from a prospective cohort of 65 patients with acute HCV infection by using a microparticle enzyme immunoassay AxSYM HCV 3.0 (Abbott Diagnostics) during the first 12 months from HCV acquisition in Rio de Janeiro, Brazil. Spontaneous viral clearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Several factors are associated with spontaneous resolution of HCV viremia, including host factors such as age, sex, ethnicity and immune response [31], [32]. The rate of spontaneous HCV resolution can range from 10% to 60% [33]. In our study, even samples with HCV viral load as low as 150 copies/mL could be successfully amplified.…”
Section: Discussionmentioning
confidence: 66%
“…Several factors are associated with spontaneous resolution of HCV viremia, including host factors such as age, sex, ethnicity and immune response [31], [32]. The rate of spontaneous HCV resolution can range from 10% to 60% [33]. In our study, even samples with HCV viral load as low as 150 copies/mL could be successfully amplified.…”
Section: Discussionmentioning
confidence: 66%
“…Understanding the prevalence and risk factors for HCV infection in regions with high prevalence could effectively prevent virus transmission to other geographical areas. Following initial exposure to HCV, two outcomes can occur, either chronic infection or spontaneous clearance of the virus, which occurs in 15%‐40% of the cases . Due to the fact that symptoms occur in only ~15% of HCV‐infected patients, the clearance rate may be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Following initial exposure to HCV, two outcomes can occur, either chronic infection or spontaneous clearance of the virus, which occurs in 15%-40% of the cases. [16][17][18] Due to the fact that symptoms occur in only ~15% of HCV-infected patients, 19 the clearance rate may be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Because we screened both for the presence of anti-HCV antibodies and HCV viral RNA, we are able to assess for spontaneous clearance of HCV. 48 , 49 The rate of spontaneous HCV resolution has been reported to range from 10% to 60% 52 and is modified by host factors such as age, sex, ethnicity, and immune response. 50 , 51 In our study, we found a general rate of spontaneous clearance of 27.65%.…”
Section: Discussionmentioning
confidence: 99%